THE IMPACT OF INTELLECTUAL CAPITAL ON FIRM VALUE WITH CAPITAL STRUCTURE AS A MODERATING VARIABLE - I Dewa Ayu Maniek Sugiantari; I Gst Ayu Eka Damayanthi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Firm Value is an investor's perception of a company's success, which can be reflected through stock prices. The wealth of shareholders and the company itself can be represented by the market price of the stock, which reflects decisions on investment, financing, and asset management. The aim of this study is to empirically examine the effect of intellectual capital on firm value and the moderating role of capital structure in influencing the relationship between intellectual capital and firm value. This study was conducted on all technology sector companies listed on the Indonesia Stock Exchange during the period of 2021-2023. The sample size was determined using a saturated sampling method, resulting in a total of 90 observations. Data analysis was performed using Moderated Regression Analysis (MRA). The results indicate that intellectual capital has a positive impact on firm value. Meanwhile, capital structure weakens the positive effect of intellectual capital on firm value. The theoretical implications of this study suggest that the findings support signaling theory and contingency theory.